2013
DOI: 10.1007/s12262-013-0835-2
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis: A Study of 48 Cases

Abstract: Necrotizing fasciitis represents a group of highly lethal infections characterized by rapidly progressing inflammation and necrosis. The aim of the study was to analyze the clinical profile, microbial flora, and predisposing risk factors in patients with necrotizing fasciitis. Lastly, we aimed to formulate a protocol for management of necrotizing fasciitis. Forty-eight cases of necrotizing fasciitis patients who reported to our hospital between April 2007 and September 2009 were included in the study. The comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…11 Singh G et al, in their study of 48 cases in 2015 observed that most of the patients were in the age group of 40-60years. 12 In the present study also most of the patients were in the age group of 40-60years.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…11 Singh G et al, in their study of 48 cases in 2015 observed that most of the patients were in the age group of 40-60years. 12 In the present study also most of the patients were in the age group of 40-60years.…”
Section: Discussionsupporting
confidence: 56%
“…This is very similar to present observation of lower extremity being the most common site of involvement, followed by upper extremity and perineum. 12 Stone et al in their study in 1972 observed perineum as the most common site, followed by lower extremity. 11 In the present study perineum was involved in only 11.67% of cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Diabetes also cause defective phagocytosis, decreased cellular immunity and micro-vascular disease with resultant ischaemia. 18,19 The patients with necrotising fasciitis can present with erythema, swelling, pain, induration, discharge, bullae formation and warmth. In our study, the patients commonly presented with warmth, induration and bullae formation (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Necrotising fasciitis is polymicrobial in nature, with most cultures yielding a mixture of aerobic and anaerobic organisms (table 1). Early diagnosis of necrotising fasciitis and aggressive treatment with surgical debridement and antibiotics determine its outcome 3. Despite excellent healthcare in developed western countries, a fulminant course of necrotising fasciitis with disabling outcomes can still occur.
Risk factors for necrotising fasciitis

Immunosuppression: medication (such as steroids, chemotherapy, infliximab) or disease (AIDS, malignancy, tuberculosis) induced

Cardiovascular diseases: arteriosclerosis, congestive heart failure, renal failure

Trauma: fractures, surgery, insect/animal bites, frostbite, intravenous drug abuse

Skin diseases: systemic lupus erythematosus, abscess, psoriasis, varicella

Gastrointestinal: diverticulitis, perirectal abscess or perforated viscus

Other: diabetes mellitus, obesity, pregnancy, advanced age

…”
Section: Descriptionmentioning
confidence: 99%